How on-site analytical techniques can help mining waste recovery and valorisation - Bruno Lemière (Discover Civil Engineering)
Abstract Mining waste recovery and valorisation is a major challenge because mining generates very large volumes of waste, and because part of this waste has to be considered a resource for the present and future needs of minerals, provided that the waste characteristics are better known. This applies to both suitability for intended use and environmental safety compliance. Due to mining waste characteristics, its reliable characterisation cannot be efficiently achieved by laboratory methods alone. A review of the main on-site characterisation methods is given, along with an evaluation of their scope and limitations. On-site methods, used as the main approach or as a complement, offer a significant gain in representativity and in time reactivity, resulting in a better cost-effectiveness of recovery evaluation and operation.